International Welfare Effects of Monetary Policy - Juha Tervala (Aboa Centre for Economics (ACE), 2011)
In this paper, I examine the international welfare effects of monetary policy. I develop a New Keynesian two-country model, where central banks in both countries follow the Taylor rule. I show that a decrease in the domestic interest rate, under producer currency pricing, is a beggar-thyself policy that reduces domestic welfare and increases foreign welfare in the short term, regardless of whether the cross-country substitutability is high or low. In the medium term, it is a beggar-thy-neighbour (beggar-thyself) policy, if the Marshall-Lerner condition is satisfied (violated). Under local currency pricing, a decrease in the domestic interest rate is a beggar-thy-neighbour policy in the short term, but a beggarthyself policy in the medium term. Both under producer and local currency pricing, a monetary expansion increases world welfare in the short term, but reduces it in the medium term.
Keywords: E32; E52; F30; F41; F44; 330; Open economy macroeconomics; monetary policy; beggar-thyself; beggar-thy-neighbour; Taylor rule; welfare analysis